2016
DOI: 10.1590/0102-3772e322214
|View full text |Cite
|
Sign up to set email alerts
|

Prototype Matching of Personality Disorders with the Dimensional Clinical Personality Inventory

Abstract: -This study aimed to investigate validity evidence of the Dimensional Clinical Personality Inventory (IDCP) through the expected associations with the five-factor model (FFM), especially in regard to the prototype matching of personality disorders. A non-clinical sample (N=94), aged between 19 and 55 years (M=25.5; SD=7.35), and 59.6% male, answered the IDCP and the NEO-PI-R for the assessment of 12 dimensions related to personality disorders and evaluation of five personality dimensions, respectively. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
(29 reference statements)
1
11
0
2
Order By: Relevance
“…The analysis covering only the 61 items kept between the IDCP and its revised version, IDCP-2, was performed considering that (a) the items kept in the revised version are empirically those which presented higher psychometric adequacy in previous studies (e.g., Carvalho & Arruda, 2016;Carvalho, Pianowski, & Miguel, 2015;Carvalho, & Sette, 2015;, 2017;Carvalho, Sette, Capitão, & Primi, 2014;Carvalho, Souza, & Primi, 2014) and (b) despite some items shared with the analysis covering the IDCP in general, it is a different grouping of predictive variables. Similarly, in the third group of analyses, only the 27 items composing the Mood Instability dimension were used, since data presented in previous studies suggested this dimension as subjacent to pathological personality functioning in general (e.g., Abela, Carvalho, Cho, & Yazigi, 2015;Carvalho, & Primi, 2016;. Finally, for the fourth group analysis (i.e., Cohen's d) the percentile 75 (d=0.60) was arbitrarily established as a cutoff for selecting the most discriminative items.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis covering only the 61 items kept between the IDCP and its revised version, IDCP-2, was performed considering that (a) the items kept in the revised version are empirically those which presented higher psychometric adequacy in previous studies (e.g., Carvalho & Arruda, 2016;Carvalho, Pianowski, & Miguel, 2015;Carvalho, & Sette, 2015;, 2017;Carvalho, Sette, Capitão, & Primi, 2014;Carvalho, Souza, & Primi, 2014) and (b) despite some items shared with the analysis covering the IDCP in general, it is a different grouping of predictive variables. Similarly, in the third group of analyses, only the 27 items composing the Mood Instability dimension were used, since data presented in previous studies suggested this dimension as subjacent to pathological personality functioning in general (e.g., Abela, Carvalho, Cho, & Yazigi, 2015;Carvalho, & Primi, 2016;. Finally, for the fourth group analysis (i.e., Cohen's d) the percentile 75 (d=0.60) was arbitrarily established as a cutoff for selecting the most discriminative items.…”
Section: Methodsmentioning
confidence: 99%
“…The Eccentricity dimension revealed correlation with the schizotypal, schizoid (Abela et al, 2015;Carvalho & Primi, 2015) and paranoid personality disorders (Carvalho & Primi, 2016). The schizotypal disorder corresponds to a functioning with social deficits marked by discomfort in interpersonal relationships, cognitive and perceptual distortions and behavioural eccentricities; the schizoid is associated to a pervasive pattern of detachment in social relations and restrictions on emotional expression in interpersonal relationships; and the paranoid functioning exposes a durable pattern of distrust in interpersonal relationships, pervaded by suspicion of intent to others and emotional liability (APA, 2013).…”
mentioning
confidence: 96%
“…9 According to Abela 17 and to Carvalho & Primi, 6 this dimension relates most closely to narcissistic personality disorder, which is expected given this disorder's diagnostic criteria. 1 This study aimed to further refine the grandiosity dimension and update it to include pathological traits typically related to narcissistic personality disorder.…”
Section: Discussionmentioning
confidence: 96%
“…9 This dimension includes feelings of pleasure obtained from external recognition, an excessive need for being admired by others, and underlying beliefs of self-worth and superiority. These feelings generate self-entitlement, grandiosity, and distrust/persecution reactions towards others.…”
mentioning
confidence: 99%